Detecting and analysing changes in consumer behaviour during life events - Darler, William (2019)
Consumer behaviour changes over time as people experience life events, stages and transitions. There has been little empirical research that analyses these changes using real world transaction data. This thesis contributes to the research on the consumer life course through the creation of two methods to predict and describe consumption behaviour during a life event. Transaction data sets from two multinational retailers are used to develop methods to 1. Detect the points in time when consumption behaviour is likely to change during a life event and predict the event-stage of new customers 2. Describe and visualise the trajectories of different customer segments over time based on the combination of items they put in their shopping baskets. These methods are demonstrated using retail data from 3.4 million customers experiencing the event of parenthood over a period of 10 years.